Avaliação de receptores similares a toll (tlrs) em monócitos de pacientes com doença de Parkinson - Rocha Sobrinho, Hermínio Maurício da (2017)
Parkinson's disease (PD) is a condition of the central nervous system (CNS), chronic and progressive, resulting from the death of brain dopamine-producing neurons. Genetic and epidemiological studies have highlighted the role of neuroinflammation in the pathophysiology of PD, emphasizing that the process of neuroinflammation is associated with the death of dopaminergic neurons. In peripheral blood or tissues, leukocytes activated by pathogen-associated molecular patterns (PAMP) and / or tissue damage (DAMP), via Toll-like receptors (TLR), produce pro and antiinflammatory mediators whose imbalance can lead to a chronic inflammation. Under physiological conditions, three subpopulations of human peripheral blood monocytes are detected: the classical monocytes (CD14++CD16-), the intermediates (CD14++CD16++) and the non-classical (CD14+CD16+), these cells present phenotypic and functional differences that can influence the characteristics of the immune response against DAMPs or PAMPs. The aim of this study was to compare the peripheral blood leukocyte potential of patients with PD or healthy individuals in the production of cytokines (TNFα and IL-10) after stimulation of these cells with TLR4 (LPS) or TLR2 / 1 (Pam3Cys) agonists, to evaluate the effect of the age of DP patients on the production of cytokines in blood cultures, to investigate the percentage of monocyte subpopulations expressing TLR1, TLR2 and TLR10, to evaluate the influence of TLR10 expression on the biological activity of TLR2 to its agonist in PBMC cultures. Two groups of patients with PD were evaluated (≤ 55 years old and ≥ 65 years old), age-matched with healthy controls (n = 26). 6 h-TNFα production was increased after TLR4 stimulation, mainly in young PD patients, whereas TLR2-induced TNFα and IL-10 levels were decreased in PD patients independent of age (p < 0.05). A reverse correlation between LPS-induced TNFα production and age was observed in PD patients and controls, but TNFα induced by TLR2 agonist was not associated with age of PD patients or controls. TNFα production induced by TLR4 but not by TLR2 was reversely associated with the age at PD onset and disease duration. No associations between UPDRS scores and cytokine levels were detected. A higher percentage of CD14++CD16+ monocyte subpopulation was observed in the blood of patients with PD compared to healthy controls, as well as a higher percentage of monocytes from patients expressing TLR10. The expression of TLR2 and TLR10 in peripheral blood monocytes from PD patients was increased relative to that of healthy controls. The results suggest that the peripheral blood leukocyte response to the TLR2 ligand is reduced in PD and that the elevation of TLR10 expression in monocytes influences inhibiting the biological activity of TLR2 to its agonist as demonstrated in the neutralization experiment of TLR10. In this study, the group of DP patients with the highest severity of the disease, evaluated by the UPDRS scale, had a lower percentage of monocytes expressing TLR10, suggesting the expression of this receptor in peripheral blood leukocytes as a possible prognostic marker for DP. These findings, together, may play an important role in the immunopathology of PD. The study of TLR cell expression in peripheral leukocytes and CNS, intracellular signaling pathways and the production of pro and anti-inflammatory mediators is necessary in order to better clarify the role of TLR in the PD pathogenesis and perhaps for the identification of biomarkers of disease prognosis in the blood PD patients.